A New Nonlinear Conjugate Gradient Coefficient for Unconstrained Optimization - Mustafa, Mamat; Mohamed, Hamoda; Mohd, Rivaie (HIKARI Ltd., 2015)
In this paper, we suggest a new nonlinear conjugate gradient method for solving large scale unconstrained optimization problems. We prove that the new conjugate gradient coefficient β k with exact line search is globally convergent. Preliminary numerical results with a set of 116 unconstrained optimization problems show that β k is very promising and efficient when compared to the other conjugate gradient coefficients Fletcher - Reeves (FR) and Polak -Ribiere – Polyak (PRP).